The Effect of Noise and Lighting on the Output of Work Production in Small and Medium-Sized Foundry Enterprises - Nurmaningsih Nurmaningsih; Widodo Hariyono; Agung Kristanto; Muhammad Syamsu Hidayat; Muhammad Syapril (PROMOTOR, 2023)
The main work environment factors which include temperature, lighting, noise, and air circulation are factors that affect the physical, mental, and psychological burden of employees. High physical, mental, and psychological burdens can affect the non-achievement of production output. This is found in Metal Casting SMEs TS Aluminum. The noise level at the TS Aluminum SMEs at the scraping workstation exceeded the normal threshold of 92.42 dB and the lighting at the scraping workstation was below the threshold of 49.8 Lux. This study was conducted to determine the effect of noise and lighting simultaneously or partially on production output at the processing workstation at SMEs TS Aluminum. This study used the multiple linear regression method, with 5 respondents. The equipment used for noise data collection is the Lutron SL-400 Sound Level Meter and lighting is measured using the Lux MeterLX101 A measuring instrument. Based on the results of statistical tests, show that simultaneous and partial noise and lighting variables have a significant positive effect on production output at the processing workstation at SMEs TS Aluminum (p-value < 0.05). Testing the value of multiple coefficients of determination obtained a percentage of 47% of the influence of noise and lighting on productivity variables, while the remaining percentage of 53% was influenced by other variables that were not studied. Suggestions for noise are that SMEs pay more attention to room capacity, pay attention to the layout of employees in filing, installation of room silencers, and workers required to use personal protective equipment (PPE). The lighting suggestion is that SMEs must add lights in every corner of the room so that the lighting is evenly distributed to all rooms.